2021
DOI: 10.1108/jtf-09-2020-0155
|View full text |Cite
|
Sign up to set email alerts
|

New experiences in nature areas: architecture as a tool to stimulate transformative experiences among visitors in nature areas?

Abstract: Purpose The purpose of this paper is to share architecture as a tool that is increasingly implemented in nature areas and its potential for stimulating transformative experiences among visitors in nature-based tourism. Design/methodology/approach Based on three examples of architecture in nature, the value of architecture to nature-based tourism is presented. Findings It was found that architecture in nature has a wide range of benefits for nature-based tourism and may form a catalyst for gaining transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The video showcased the Mosque City of Bagerhat. Other studies suggested various actions toward positive experience in authenticity such as using nature-based materials in architecture (Wielenga, 2021), providing the opportunity to observe the actual production of tourism products (Kim and Bonn, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The video showcased the Mosque City of Bagerhat. Other studies suggested various actions toward positive experience in authenticity such as using nature-based materials in architecture (Wielenga, 2021), providing the opportunity to observe the actual production of tourism products (Kim and Bonn, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…This transformation, aligns with a stronger focus on sustainable and regenerative tourism with nature and communities at its heart. Wielenga (2023) uses architecture as a framing tool for nature thus stimulating transformative experiences among visitors in nature-based tourism. Pongsakornrungsilp and Pongsakornrungsilp (2023) study demonstrate’s how the circular economy is employed to drive the sustainability of the tourism industry in Krabi, Thailand, through the concept of mindful consumption and service-dominant logic.…”
Section: Nature and Sustainable Tourismmentioning
confidence: 99%